PENGARUH PEMBERIAN JUS KECAMBAH KACANG HIJAU (Vigna radiata (L.) R. Wilczek)TERHADAP KUALITAS SPERMATOZOA DAN SPERMATOGENESIS MENCIT JANTAN GALUR SWISS - Yance Anas; Nur Chakim; Suharjono Suharjono (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT Efficacy of mung bean sprouts as natural fertility enhancer for men was not widely investigated and published. The objective of this study is to investigate the effect of mung bean sprout’s juice on male Swiss mice spermatozoa quality and spermatogenesis. An experimental study performed with randomized matched two-group post test only design approach. Thirtymale mice were dividedinto fivegroups randomly, which consist of a control group (CMC25mL/kg BW/day); d-α-tocopherol group (556 IU/kg BW/day) and three mung beans sproutjuice groups (33, 66 and 132) mg/kg BW/day. Mice treated every dayfor 20days orally. Micewere sacrificed; testis and epididymis were collected and examined. The spermatozoa quality (count, progressive motility and normal morphology) and spermatogenesis observed. The results showedthatmung bean sproutsjuice treatment (33, 66 and 132) mg/Kg BW/day for 20 days did not enhance male Swiss strain mice fertility. Spermatogenesis score, count and normal morphology spermatozoa that receive treatment with mung bean sprout juice was not significantly different to the control group (p>0.05). Conversely; mung bean sprouts juice treatment lead to decrease male Swiss strain mice spermatozoa progressive motility (p<0,05). Keywords: Mung bean sprouts (Vigna radiata (L.) R.Wilczek) juice, spermatozoa quality, spermatogenesis.